CONSTRUCTIVISTIC APPROACH IN PHYSICS AND TRECHNOLOGY INSTRUCTION - CERNANSKY, Peter; RAKOVSKA, Maria (Trends in education, 2010)
The article introduces constructivistic approach in physics and/or technology instruction. important rules for writing of articles into report which is preparing for the conference.
Keywords: constructivistic approach in physics and technology instruction; activating methods in education; aplets